2018
DOI: 10.1177/1540415317750085
|View full text |Cite
|
Sign up to set email alerts
|

Uso Del Condón en Adolescentes Nahuas, un Modelo Explicativo

Abstract: En México, la población indígena supera los siete millones de habitantes, en Puebla el grupo más representativo es el Náhuatl. Sin embargo, las condiciones de vida, salud, educación y transporte son precarias para esta población. En los adolescentes, las responsabilidades como el matrimonio, la familia y los compromisos ante la comunidad, favorecen conductas de riesgo sexual que dificultan su desarrollo económico, social y reproductivo. El objetivo fue proponer un modelo explicativo del uso del condón en adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
4
3
0
Order By: Relevance
“…In terms of ethnic identity, it was found that adolescents who expressed a greater sense of attachment to their ethnic group through exploration and learning activities were more interested in safe sexual behaviors such as the correct and consistent use of condoms during sexual intercourse. This result is congruent with that reported by Meneses-Tirado and collaborators [5], who detailed in a model that adolescents who showed greater commitment to their ethnic group were less likely to have sexual intercourse, and that ethnic identity was a protective factor for safe sex, for a lower number of sexual partners, and for proposing the first sexual relation. However, Nava-Navarro et al [6] and Bukuluki et al [7] reported that greater ethnic identity increased the likelihood of STI presentation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In terms of ethnic identity, it was found that adolescents who expressed a greater sense of attachment to their ethnic group through exploration and learning activities were more interested in safe sexual behaviors such as the correct and consistent use of condoms during sexual intercourse. This result is congruent with that reported by Meneses-Tirado and collaborators [5], who detailed in a model that adolescents who showed greater commitment to their ethnic group were less likely to have sexual intercourse, and that ethnic identity was a protective factor for safe sex, for a lower number of sexual partners, and for proposing the first sexual relation. However, Nava-Navarro et al [6] and Bukuluki et al [7] reported that greater ethnic identity increased the likelihood of STI presentation.…”
Section: Discussionsupporting
confidence: 91%
“…These data confirm that social and psychological perceptions of ethnicity may be a source of support that promotes healthy development and protects adolescents from exposure to sexual risk; it may also be positively associated with health and risk behaviors with partners [5]. The Nahua community in Mexico is increasing and is in permanent contact with society.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These living conditions increase the vulnerability of adolescents who often take risks in sexual relations regardless of consequences, including STIs and unwanted pregnancies. Sexual behavior of Indigenous adolescents incorporates meanings and practices influenced by the interaction of personal biological, affective, and cognitive factors, as well as interpersonal and sociocultural environmental factors [ 5 ]. A common adolescent risk in sexual relationships is sex without condoms.…”
Section: Introductionmentioning
confidence: 99%
“…The Model of Safe Sexual Behavior in Nahua Adolescents (MOCSSAN) developed by Meneses-Tirado and collaborators [ 5 ] provided the theoretical basis for this study. This model describes the relationship between personal and environmental factors and how they influence safe sexual behavior among Indigenous adolescents.…”
Section: Introductionmentioning
confidence: 99%